A STUDY ON CEILING PAINTINGS OF THIRUPARUTHIKUNDRAM TEMPLE - Sujatha, Erata; Rao, Kota Mrutyunjaya (International Journal of Research -GRANTHAALAYAH, 2025)
Thiruparuthikundram, historically known as Jain Kanchi, this area is a testament to the glory of Jainism. The main deity in this temple is Lord Mahavira, Dharmadevi is seen on the left side of Mahavira. Jain Kanchi is located on the right bank of the Vegavathi River, within the city limits of Kanchipuram. This Jain temple is evidence of the presence of Jainism in Kanchipuram in ancient times. This temple is known by other names like TrailokyaNatha Temple, Vardhmana and Jeenaswamy, and dates belong to the 8th and 9th centuries. Thiruparuthikundram is one of the four educational institutions for Digambara Jains in India, the other three being in Delhi, Kolhapur and Penukonda. Jain paintings based on the lives of the Tirthankaras and other stories depicted on the ceiling of the Sangita Mandapam are painted.